1998
DOI: 10.2307/3151846
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Consumers' Tendency to Combine Multiple Shopping Purposes and Destinations

Abstract: Investigating consumers' tendency to combine multiple shopping purposes and destinations Dellaert, B.G.C.; Arentze, T.; Bierlaire, M.; Borgers, A.; Timmermans, H.J.P. Publication date: 1997 Link to publication Citation for published version (APA):Dellaert, B. G. C., Arentze, T., Bierlaire, M., Borgers, A., & Timmermans, H. J. P. (1997). Investigating consumers' tendency to combine multiple shopping purposes and destinations. (CentER Discussion Paper; Vol. 1997-94). CentER. General rightsCopyright and moral ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(63 citation statements)
references
References 22 publications
(1 reference statement)
3
57
0
3
Order By: Relevance
“…Since a considerable number of authors have identified these factors as drivers of retail related attractiveness we present the following hypotheses Anselmsson, 2006;Ruiz et al, 2004;Baker et al, 2002;Leo & Philippe, 2002;Van Kenhove et al, 1999;Dellaert et al, 1998;Bearden, 1977;Bellenger, 1977). The offer of an urban place also contains non retail service businesses.…”
Section: (Retail and Non Retail) Offer Of Urban Retail Agglomerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a considerable number of authors have identified these factors as drivers of retail related attractiveness we present the following hypotheses Anselmsson, 2006;Ruiz et al, 2004;Baker et al, 2002;Leo & Philippe, 2002;Van Kenhove et al, 1999;Dellaert et al, 1998;Bearden, 1977;Bellenger, 1977). The offer of an urban place also contains non retail service businesses.…”
Section: (Retail and Non Retail) Offer Of Urban Retail Agglomerationsmentioning
confidence: 99%
“…This retail tenant mix (ξ 3 ) can be described by the range (x 31 ), the attractiveness (x 32 ) and the number of wellknown stores (x 33 ) (e.g., Dellaert et al, 1998;Prendergast et al, 1998). The retail offer of the tenants can be characterised, firstly, by the merchandise value offered with this being operationalised by the overall price level (x 41 ), the quality level (x 42 ) and the price-quality ratio (x 43 ) (e.g., Severin et al, 2001;van Kenhove et al, 1999).…”
Section: (Retail and Non Retail) Offer Of Urban Retail Agglomerationsmentioning
confidence: 99%
“…Ofrecer una amplia selección de productos puede contribuir a reducir los costes percibidos en relación con los esfuerzos que se han de lle-var a cabo en cada acto de compra, al margen de facilitar el propio acto de compra. Por tanto, una mayor variedad del surtido puede aumentar la conveniencia que el consumidor obtiene, y por ende, su satisfacción (Dellaert et al, 1998). Comercializar marcas propias constituye también un activo de carácter estratégico para estos distribuidores puesto que contribuye a incrementar la variedad del surtido y a lograr otros objetivos relacionados con el posicionamiento a largo plazo (Binninger, 2008;Corstjens y Lal, 2000;Gomez y Rubio, 2006).…”
Section: Marco Conceptualunclassified
“…At the same time, there have been other studies directed toward understanding geographical interactions between spatial units, and their effects on choice behavior, but with limited to no consideration of spatial cognition/preference issues [see, for example, (9), (10), (11), (12), (13), provide a review of such studies]. Few earlier studies have comprehensively considered both cognitive/preference concepts at the decision maker level, as well as interactions between spatial choice units [but see (14) and (15); the reader is referred to Sivakumar (16) for a comprehensive survey of the literature on location choice modeling].…”
Section: The Current Studymentioning
confidence: 99%